2017
DOI: 10.21037/qims.2017.09.03
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of enhancement-perfusion mismatch in differentiation of CNS lymphomas from other enhancing malignant tumors of the brain

Abstract: Background: Surgical planning and treatment options for primary or secondary central nervous system lymphomas (PCNSL or SCNSL) are different from other enhancing malignant lesions such as glioblastoma multiforme (GBM), anaplastic gliomas and metastases; so, it is critical to distinguish them preoperatively.We hypothesized that enhancement-perfusion (E-P) mismatch on dynamic susceptibility weighted magnetic resonance (DSC-MR) perfusion imaging which corresponds to low mean relative cerebral blood volume (mean r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…20 Studies by Goyal et al, who also examined rCBV, You et al, who examined arterial spin labelling MRI, and Ko et al, who used ADC and AUC in the tumour and surrounding areas for comparison, all found significant differences between PCL and other brain tumours, mostly glioblastomas. [21][22][23] ADC values measured from DWI have been shown to be inversely related to tumour cellularity. 16 ADC values in PCL are reported to be significantly lower than those in glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…20 Studies by Goyal et al, who also examined rCBV, You et al, who examined arterial spin labelling MRI, and Ko et al, who used ADC and AUC in the tumour and surrounding areas for comparison, all found significant differences between PCL and other brain tumours, mostly glioblastomas. [21][22][23] ADC values measured from DWI have been shown to be inversely related to tumour cellularity. 16 ADC values in PCL are reported to be significantly lower than those in glioblastomas.…”
Section: Discussionmentioning
confidence: 99%
“…DSC-PWI has the potential to provide hemodynamic information about PCNSLs. [28][29][30][31] In normal subjects, the CGM structures have the highest blood volume, followed by DGM and WM structures.…”
Section: Resultsmentioning
confidence: 99%
“…DSC-PWI has the potential to provide hemodynamic information about PCNSLs [27][28][29][30]. In healthy subjects, the CGM structures have the highest blood volume, followed by DGM and WM [31].…”
Section: Discussionmentioning
confidence: 99%